The gift is kindness: imagination in reading and producing images in Early Childhood Education (Olhar de Professor, 2025)
This article examines an experience report on the experiences of 4 and 5 year old children with the languages of visual arts in an Early Childhood Education institution, mediated by a male and female teacher. The objective of this work is to present an analysis of how the appreciation of works of Contemporary Art and the production of images by children are interrelated, considering teaching mediation and children's protagonism. The methodology is structured around an experience report, based on the observation of children's relational demands, on the appreciation of the audiovisual Cuerdas, conceived as a production of Contemporary Art, and on the proposition of other experiences with art. The results show that children, when watching the video, spontaneously attributed meanings to it, relating it to the theme of kindness. Based on this experience, the teachers proposed a new experience, in which the children created images through drawing, painting and collage, as a way of giving gifts to each other. The conclusions suggest that such experiences favor the development of significant interfaces between Contemporary Art, image reading and childhood, in addition to promoting children's protagonism and imagination as essential tools for building meaning in children's lives.
Keywords: Early Childhood Education; Teaching